Hydration Thermodynamics and Hydrodynamic (Stokes) Radius of the Lanthanide Ions - muhammed J. Kadhim; Maher Ibraheem Gamaj (Iraqi Journal of Physics, 2020)
Many biochemical and physiological properties depend on the size of ions and the thermodynamic quantities of ion hydration. The diffusion coefficient (D) of lanthanide (III) ions (Ln+3) in solution assumed (1.558-1.618 ×10−9 m2 s−1) by Einstein–Smoluchowski relation. The association constant (KA) of Ln+3 ions was calculated (210.3-215.3 dm3 mole-1) using the Shedlovsky method, and the hydrodynamic radius calculated (1.515-1.569 ×10−10 m) by the Stokes-Einstein equation. The thermodynamic parameters (ΔGo, ΔSo) also calculated by used suitable relations, while ΔHo, values are obtained from the literature. ΔGo, for ion hydration, has negative values in the range (13.25-13.30 KJ/mole), and a negative ΔSo, results have been shown in the limit (11.016-12.506 KJ/ K. mole).